Analisis Pengaruh Persepsi Harga Ritel, Store Atmosphere dan Promosi, Terhadap Motivasi Konsumen Berbelanja Rita Mall Tegal - Sari Wiyanti (Journal of Innovative and Creativity, 2025)
However, after Covid-19, it became a mall with expensive prices. The mall's atmosphere tended to be static and boring, and the lack of promotions caused consumers' motivation to shop at Rita Mall Tegal to decline. The purpose study was to analyze the decline in consumer motivation to shop at Rita Mall Tegal and the factors that influenced it, such as retail price perception, store atmosphere, and promotions. This research methods both qualitative and quantitative research approaches. The sample size for this study is 100 respondents, with non-probability sampling using the accidental sampling method. The data used are primary data, which will be analyzed using SPSS 25. The results of this study, multiple linear regression analysis of the Retail Price Perception (X1) variable on Consumer Motivation (Y) is positive at 0.695 and the t-test result is tcount > ttable, namely 3.462 > 1.661 with a sig. value of 0.001 < 0.05, meaning that H1 is accepted. The multiple linear regression analysis of the Store Atmosphere Perception (X2) variable on Consumer Motivation (Y) yielded a positive value of 0.349, and the t-test value was t-calculated > t-table, i.e., 1.983 > 1.661, with a significance level of 0.049 ≤ 0.05, meaning that H2 is accepted. The multiple linear regression analysis of Promotion Perception (X3) on Consumer Motivation (Y) has a positive value of 0.349, and the t-test result shows that the calculated t-value is greater than the critical t-value, i.e., 2.092 > 1.661, with a significance level of 0.042 ≤ 0.05, meaning that H3 is accepted. The F-test result shows Fcalc > Ftab, i.e., 3.058 > 2.696, with a significance level of 0.032 ≤ 0.05, meaning H4 is accepted. The conclusion is that consumer motivation in shopping at Rita Mall Tegal is influenced by the perception of low retail prices, store atmosphere with lighting, air-conditioned rooms, attractive exterior and interior design, and aggressive promotions through social media carried out by Rita Mall Tegal.